Historical Time Series Perspectives on Competitive Balance in NCAA Division I Basketball. (August 2015) - Mills, Brian M.; Salaga, Steven
In this article, we extend the literature on competitive balance to National Collegiate Athletic Association (NCAA) Division I men's basketball. We track historical within-conference balance utilizing measures accounting for game-level uncertainty and consecutive season uncertainty. We find a host of structural changes in competitive balance across the sport that align closely with the GI Bill, racial integration, and the split of the NCAA into three divisions. We also find evidence of short-term improvements in balance following individual conference-level regulation specific to the Ivy League.